Stability and infectivity of enteroviruses on dry surfaces: Potential for indirect transmission control - Pichamon Sittikul; Pimolpachr Sriburin; Jittraporn Rattanamahaphoom; Warisa Nuprasert; Nipa Thammasonthijarern; Janjira Thaipadungpanit; Weerawan Hattasingh; Nathamon Kosoltanapiwat; Pilaipan Puthavathana; Supawat Chatchen (Elsevier, 2023)
Hand, foot, and mouth disease (HFMD) is a contagious disease mainly occurring in young children, and outbreaks commonly occur among young children in the Asia-Pacific region including Thailand. Moreover, the World Health Organization (WHO) monitors HFMD in the Western Pacific region to detect outbreaks and other significant events by the Regional Event Based Surveillance System. HFMD is mainly caused by a group of enteroviruses (EVs) transmitted through direct contact (person to person) and indirect contact with contaminated objects (surface-to-hand). However, few studies have examined the surface stability of EVs. In this study, we investigated the stability of enterovirus A71 (EV-A71) and coxsackievirus A16 (CVA16) on three different dry surfaces (wood, plastic, and stainless steel) using the endpoint titration using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) staining of viable cells and real-time polymerase chain reaction (viral genome detection). The results revealed that virus infectivity dramatically decreased within a few hours on dry surfaces. However, viral RNA could be detected on dry surfaces for up to 28 days. Concerning heat inactivation, both EV-A71 and CVA16 were inactivated after exposure to 60°C for 15 min. Information on virus stability on different dry surfaces will provide useful information for HFMD transmission control.